Legal Political Analysis in The State Budget (State Accountability) - Mutia Evi Kristhy; Dadang Siswanto; Datman Ketaren (Journal of Social Science, 2022)
Accountability is still a major issue in the public sector in Indonesia. Lack of responsibility is very visible, and over time, it has become the dominant aspect of organizational culture, especially in budget management. This research aims to review the Political Analysis of Law in the State Budget (State Accountability). The research method used in this study is qualitative with the literature review. The results show that inherently, politicians are vulnerable to taking advantage of the government's position to enrich themselves, their colleagues and their relationships. Therefore, to maximize the budget so that it is right on target, on time, and with the right quality, it is necessary to supervise the Financial Supervisory Agency (BPK), which has an important role in carrying out audits of the management and state financial responsibility.